Analisis UX E-PPT Universitas XYZ dengan Metode User Experience Questionnaire - Kevin Agustin Purba Purba; Umar Rahman Zidan; Muhammad Azyumardi Azra; Fathoni (SMARTICS Journal, 2025)
Digital transformation in academic administrative services demands systems that are efficient and user-experience oriented. This study aims to analyze the user experience of the e-PPT website of the Faculty of Computer Science at XYZ University, which functions as an academic administrative service platform. The research employs the User Experience Questionnaire (UEQ) method, which measures six core aspects of user experience: attractiveness, efficiency, perspicuity, dependability, stimulation, and novelty. A total of 40 active students from the Faculty of Computer Science at XYZ University participated by completing the UEQ questionnaire. The analysis results indicate that all UEQ dimensions received low scores, with the novelty dimension scoring negatively. Benchmarking against similar systems revealed that the e-PPT website falls within the lowest quartile (bottom 25%) across all scales. These findings underscore the urgent need for comprehensive improvements in the website’s design and functionality to enhance the quality of digital academic services in the future.